OWE-012 Nationwide population-based evaluation of mortality and cancer-risk in young patients with ulcerative colitis/primary sclerosing cholangitis. (8th June 2018) - Trivedi, Palak; Mytton, Jemma; Evison, Felicity; Kamarajah, Sivesh Kathir; Reece, Jessamy; Iqbal, Tariq; Cooney, Rachel; Thompson, Fiona; Walmsley, Martine; Ferguson, James; Hirschfield, Gideon
Abstract : Introduction: Advancing age is proposed as a risk factor for mortality in primary sclerosing cholangitis (PSC) (Trivedi*Weismuller* et al. Gastro. 2017). However outcomes against a matched control population need evaluation. Our aim was to provide data-driven prioritisation of unmet need by comparing pts. with ulcerative colitis (UC) and coexisting PSC vs an age-matched cohort with UC alone in a stratified outcomes' analysis. Method: A population-based study was performed via linkage to the national Hospital Episode Statistics registry, which records every adult (>18 y of age) hospital attendance, admission or clinic event within England since 2006. Across the entire registry we captured all incident cases of UC alone (group I); and UC with an established diagnosis of PSC, or UC diagnosed with PSC subsequently (group 2). Case finding/definition was as per Jess et al (Gastro 2012), by applying ICD10 codes for UC overall (inclusion K51), UC/PSC more specifically (inclusion K51 +K83.0) and excluding other causes of liver injury (K70–77, K80.3/4, B16–19). Cases were captured till 03/2015; follow-up ending 1y thereafter. Event rates (colectomy, colorectal cancer [CRC], liver transplantation [LT]/death, and all-cause mortality) were stratified according to age strata at UC diagnosis. Results: Over 10 years, 1 28 694 incident UC cases were identified (annualised incidence/100, 000 population: 23.8 in 2006; rising to 25.1 in 2015). Of this group, 2124 were diagnosed with PSC at some point (incidence in 2006 and 2015: 0.29 and 0.4, respectively). Observing the UC cohort in entirety, we observed 210 1 st LT (206 in group 2), 9413 individuals who came to colectomy, 1, 208 CRC cases, and 11 177 pt. deaths. The leading cause of mortality was coronary disease (1%) in group 1; whereas liver-related death (5.9%), cholangiocarcinoma (4.6%) and CRC (1%) predominated in group 2. The incidence rate ([IR]/1000-pt.yrs.) was greater in the UC/PSC group for colectomy (17.3 vs 13.7), CRC (5.6 vs 1.5), LT/death (38.5 vs 15.1), and all cause mortality (26.4 vs 15.1); p<0.001 for all. Time-dependent Cox regression validated the negative impact of PSC onset for each endpoint (time-dependent adjusted hazard ratio: 1.62, 3.31, 2.47 and 1.62, respectively; p<0.001 for all). Compared to UC alone, the standardised incidence ratio (SIR) for CRC was greatest in UC/PSC of young presenting age (<40 y.); a 7-fold increase (figure 1A ). This contrasted to pts. diagnosed above age 40 (SIR 4). Although absolute mortality rate was elevated in older ages (figure 1B) it was in young pts. with UC/PSC that the contrast vs UC alone was most evident for 5 year. (1.6% vs 0.4%) and 10 year. survival (3.6% vs 0.6%); a 4 and 6-fold increase, respectively. Indeed, standardised mortality (SMR) was the greatest for patients diagnosed age < 40 years., and plateaued with older age at diagnosis (figure 1C ). Conclusion: In pts. diagnosed aged < 40 years. with UC, development of PSC is associated with 6-fold increase in mortality and 7-fold increased risk of CRC. Within IBD cohorts, those diagnosed at a young age with PSC have a heightened and disproportionate unmet need for life-prolonging therapies.